2007
DOI: 10.1007/s00216-007-1505-7
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry and amperometric detection of tetracyclines at multi-wall carbon nanotube modified electrodes

Abstract: The voltammetric behaviour and amperometric detection of tetracycline (TC) antibiotics at multi-wall carbon nanotube modified glassy carbon electrodes (MWCNT-GCE) are reported. Cyclic voltammograms of TCs showed enhanced oxidation responses at the MWCNT-GCE with respect to the bare GCE, attributable to the increased active electrode surface area. Hydrodynamic voltammograms obtained by flow-injection with amperometric detection at the MWCNT-GCE led us to select a potential value E(det) = +1.20 V. The repeatabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 27 publications
1
46
0
3
Order By: Relevance
“…Therefore, there have been lots of efforts to develop the sensitive and selective biosensor systems for detection of these antibiotics in contaminated food products and pharmaceutical preparations. However, the previously reported methods such as dipstick colorimetric method (Link et al, 2007), amperometric detection method using multi-wall carbon nanotubes (Vega et al, 2007), and antibody-based colorimetric methods (Weber et al, 2005) were found to be neither specific nor sensitive, due to the high structural similarity of TC derivatives, which could be a hurdle in their selective recognitions.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, there have been lots of efforts to develop the sensitive and selective biosensor systems for detection of these antibiotics in contaminated food products and pharmaceutical preparations. However, the previously reported methods such as dipstick colorimetric method (Link et al, 2007), amperometric detection method using multi-wall carbon nanotubes (Vega et al, 2007), and antibody-based colorimetric methods (Weber et al, 2005) were found to be neither specific nor sensitive, due to the high structural similarity of TC derivatives, which could be a hurdle in their selective recognitions.…”
Section: Introductionmentioning
confidence: 95%
“…However, this method is neither sensitive for detection of TCs nor distinguishes the other members of TET derivatives in contaminants. In another study, an improved amperometric detection method for TCs was reported by using multi-wall carbon nanotube-modified electrodes (detection limit: 0.09-0.44 lM of oxytetracycline) [15]. Immune-based colorimetric methods employing ELISA-type format which utilize antibodies had the detection limit of TCs in ng/mL range [16], but these sensitive detection techniques for TCs are often expensive, labor intensive, and time-consuming.…”
Section: Introductionmentioning
confidence: 98%
“…The oxidation of tetracycline (TC) has been reported by gold [12], ruthenium oxide-hexacyanoruthenate (RuO-RuCN) [13] or multiwall carbon nanotubes (MWNTs) [14] modified electrodes. However, the tetracycline antibiotics, such as tetracycline, chlortetracycline and oxytetracycline, contain the same phenolic and di(methyl)amino substituents.…”
Section: Introductionmentioning
confidence: 99%